Case Report: CD40LG Arg203Ile variant underlies atypical phenotype of X-linked hyper IgM syndrome - Nishikawa, Takuro; Tomomasa, Dan; Hijikata, Atsushi; Kasabata, Hiroshi; Okamoto, Yasuhiro; Ochs, Hans D.; Kanegane, Hirokazu (Frontiers in Immunology, 2025)
Hyper IgM syndrome (HIGM) is a rare immunodeficiency caused by impaired immunoglobulin class switching, leading to recurrent infections. The present report describes the case of an 18-year-old man initially diagnosed with common variable immunodeficiency at 3 years of age. Genetic analysis revealed a hemizygous CD40LG missense variant (p.Arg203Ile) associated with X-linked HIGM (XHIGM). Structural and flow cytometric analyses indicated normal CD40 ligand (CD40L) expression on activated CD4+ T-cells but impaired CD40 binding, indicating disrupted immune signaling. Notably, the patient experienced neither bacterial infections requiring hospitalization nor opportunistic infections during 15 years of immunoglobulin replacement therapy. These findings indicate that the p.Arg203Ile variant destabilizes CD40L–CD40 interactions without affecting CD40L expression, suggesting a hypomorphic phenotype. This report highlights the importance of combining genetic testing with functional analysis when evaluating atypical XHIGM presentations to predict clinical severity and provide a scientific basis for personalized treatment strategies. Additional studies are required to assess the long-term outcomes and potential curative therapies for similar cases.